Studi Uniformitas Dosis Radiasi CT Scan pada Fantom Kepala yang Terletak pada Sandaran Kepala - Retnoningsih, Dwi Siwi; Anam, Choirul; Setiabudi, Wahyu (JURNAL SAINS DAN MATEMATIKA, 2012)
The research on the impact of tube current andÂ tube voltageÂ on uniformity of the point dose in the head phantom was placed on the table, had been conducted. The research was carried out on the CT Scan machine, Siemens Somatom Emotion 6. The detector used was CT dose profiler and Piranha Electrometer 556. The phantom was head phantom with PMAA material with diameter 16 cm and length 15 cm. The measurement of point dose carried out by using axial mode. The measurement conducted in five points inside the head phantom. In this research, the tube current and tube voltage were varied. The results show that the point dose on the head phantom was placed on the table is non-uniform. At the bottom of the phantom, the dose is lower to below 50% than at the top of the phantom. Â Keywords: CT Scan, Dose uniformity, Point Dose, CTDI